Risk of psoriasis in people with hidradenitis suppurativa: A systematic review and meta-analysis - Gau, Shuo-Yan; Preclaro, Ivan Arni C.; Wei, James Cheng-Chung; Lee, Chien-Ying; Kuan, Yu-Hsiang; Hsiao, Yu-Ping; Juang, Sin-Ei; Ma, Kevin Sheng-Kai (Frontiers in Immunology, 2022)
Background Hidradenitis suppurativa were associated with comorbidities in various organ systems. Inflammatory dermatological diseases such as pyoderma gangrenosum were reported to be associated with hidradenitis suppurativa. Nevertheless, as for the association between hidradenitis suppurativa and psoriasis, evidences were insufficient. In many studies, the association between psoriasis and hidradenitis suppurativa has been reported. However, some evidence seems to be controversial. The purpose of the systematic review and meta-analysis was to assess whether there was significant association between HS and psoriasis. Methods On June 01, 2022, we appraised 2,795 articles from databases including PubMed, Web of Science and Embase. Search syntaxes were based on ‘hidradenitis suppurativa’ or ‘acne inversa’ with “psoriasis”, “comorbidities” or ‘epidemiology’. Synonyms were determined based on MeSH terms and Emtree. Observational results that evaluated the odds ratio for people with hidradenitis suppurativa who had psoriasis were extracted for qualitative synthesis. Results After the selection process of the initial 2,795 studies, ten observational studies, including 3 cohort studies, 1 case-control study, and 6 cross-sectional studies, were extracted for critical appraisal. Based on the integration of 7 studies (with more than 560,000 participants included), people with hidradenitis suppurativa had a higher risk of having psoriasis, with a 2.67-fold risk (95% CI, 1.84, 3.87). The association remained in the sensitivity analyses utilizing strict adjustment models. In the analysis that only included studies with a similar study design and adjustments in obesity-related factors, the risk of people with hidradenitis suppurativa having psoriasis was 3.24 (95% CI, 2.27, 4.62). In male patients with HS, the risk of having psoriasis was 4.30-fold higher than male patients without HS (95% CI, 2.37, 7.78). Likewise, in an analysis including 3 cross-sectional studies, the risk of female HS patients having psoriasis was 3.94-fold higher than female HS-free patients (95% CI, 2.34, 6.63). Conclusions The co-occurrence of hidradenitis suppurativa and psoriasis can greatly increase the burden of the disease. Psoriasis could be one of the critical comorbidities of hidradenitis suppurativa and should be recommended for future screening and follow up. The association between the two diseases should be kept in mind in managing hidradenitis suppurativa patients. More prospective studies are needed to establish the true magnitude of the association between psoriasis and hidradenitis suppurativa.